Peluang Ekonomi Budi Daya Maggot melalui Pemanfaatan Sampah Organik di RW 12 Desa Ciwaruga - Sartika, Euis; Yuliah, Siti; Hadiani, Fatmi; Binarto, Agus; Lusiani, Anie (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The main problem facing the city of Bandung is a sharp increase in the volume of waste, followed by a rapid increase in population and changes in people's lifestyles. The volume of waste in the city of Bandung will reach 1,594.18 tons per day in 2022, which is dominated by food waste at 44.52%. Thermal processing of waste, such as RDF (refuse-derived fuels) which can be used as fuel for PLTSa incinerators, is still hampered. Ciwaruga Village, RW 12 is a densely populated area, waste handling has not been managed well, plus immigrants are increasingly contributing to waste production. Polban plays a role in helping solve the waste problem through PKM activities. The methods used are socialization, training, technical guidance, mentoring, evaluation and program sustainability. PKM activities emphasize organic waste management through maggot cultivation. The existence of a community of catfish farmers in RW 12 is the reason why the idea of ​​cultivating maggots as an alternative to catfish feed emerged, considering that the price of catfish feed is increasing. The protein content of maggots is very good for the growth of catfish, as well as complementary food for chickens. Maggot leftover food (kasgot) can be used as fertilizer. Maggots consume twice their body weight in food a day. For this reason, maggot cultivation is the right solution to reduce organic waste. PKM activities focus on developing maggot cultivation on a larger scale, namely the RW scale. Supported by waste shredding machine technology so that waste is consumed more easily and quickly by maggots. Considering the benefits of maggots, it is hoped that this can motivate people to become entrepreneurs in maggot cultivation as additional income.